Variabilita sinic v elektronovém mikroskopu - Šmarda, Jan (Masaryk University Press, 2019)
The publication presents randomly selected reproductions of images of cell structure, which the author photographed in a transmission electron microscope, from ultrathin sections of their four species of three single-celled genera of the order Chroococcales and nine species of six genera of the fibrous order Oscillatoriales.